2022
DOI: 10.13057/biodiv/d230515
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' lives and adaptation strategies toward the forest and peatland fires in Indonesia: Evidence from Central and South Kalimantan, Indonesia

Abstract: Abstract. Rozaki Z, Nopembereni ED, Rahayu L, Rahmawati N, Murhidayah ML, Rejeki TM, Ariffin AS, Azizah SN, Tjale MM. 2022. Farmers' lives and adaptation strategies toward the forest and peatland fires in Indonesia: Evidence from Central and South Kalimantan, Indonesia. Biodiversitas 23: 2379-2388. The frequency of forest and peatland fires in Kalimantan is high yearly, impacting many farmers’ agricultural activities and the environment, especially in the dry season. Farmers conduct agricultural activities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Sebaliknya, frasa kolaborasi multipihak menjadi sangat bermakna karena selaras dengan riset-riset sebelumnya yang menemukan fenomena kerja sama antar aktor dari beragam level pemerintahan (lokal, daerah, nasional, dan internasional). Dalam konteks restorasi gambut, istilah yang digunakan para peneliti untuk membungkus fenomena kerja sama antar aktor sangat beragam, mulai dari partnership (Adriani et al 2022;Nugroho, Darwo, and Yuniarti 2021;Sayer et al 2021)collective action (Jalil et al, 2021), multistakeholder collaboration (Puspitaloka et al, 2020), hybrid governance (Puspitaloka et al, 2021), interstakeholder coordination (Rozaki et al, 2022).…”
Section: Jejaring Konflik Antar Aktorunclassified
“…Sebaliknya, frasa kolaborasi multipihak menjadi sangat bermakna karena selaras dengan riset-riset sebelumnya yang menemukan fenomena kerja sama antar aktor dari beragam level pemerintahan (lokal, daerah, nasional, dan internasional). Dalam konteks restorasi gambut, istilah yang digunakan para peneliti untuk membungkus fenomena kerja sama antar aktor sangat beragam, mulai dari partnership (Adriani et al 2022;Nugroho, Darwo, and Yuniarti 2021;Sayer et al 2021)collective action (Jalil et al, 2021), multistakeholder collaboration (Puspitaloka et al, 2020), hybrid governance (Puspitaloka et al, 2021), interstakeholder coordination (Rozaki et al, 2022).…”
Section: Jejaring Konflik Antar Aktorunclassified
“…Farmers' adoption of technology is signi􀅫icantly in􀅫luenced by social networks based on the principle of closeness in an area where there are clear social networks with kinship, geographical relation-ships, and industry-predestined relationships. Social in􀅫luence has a complex role in the adoption of new technology, as various studies have shown ((ROZAKI et al, 2022); (Shi et al, 2022)). Stated differently, social in􀅫luence might be de􀅫ined as the extent to which individuals perceive that sig-ni􀅫icant others concur with their behavior or technological decisions (Skaalsveen et al, 2020).…”
Section: Literature Review Social In􀅮luence and Willingness To Adopt ...mentioning
confidence: 99%
“…The region's Gross Regional Domestic Product distribution shows that South Kalimantan's economy is still mostly based on agriculture. The importance of the agricultural, forestry, and 􀅫isheries farms was highlighted in 2017 when it contributed 14.59% of the GRDP (ROZAKI et al, 2022). Interestingly, mining and excavation contributed far more to South Kalimantan's GDP than forestry, agriculture, and 􀅫isheries combined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, the volume of Source: [12] Food security crisis are not limited to mineral soils. Fragile peatlands are experiencing greater pressure due to climate change [13,14]. One of the causes of global climate crisis is peatland fires that happen around the world, particularly in Indonesia.…”
Section: Introductionmentioning
confidence: 99%